Respuesta :

Given:

The system of equation:

[tex]x+y = -4[/tex] -------- (1)

[tex]y = x^{2} -6x[/tex] --------- (2)

To find the values of x and y.

We will use substitution method.

From (1) we get,

[tex]y = -4-x[/tex]

We will put the value of y in (1) and we get,

[tex]-x-4 = x^{2} -6x[/tex]

or, [tex]x^{2} -5x+4= 0[/tex]

Now we will apply middle term factor method.

  [tex]x^{2} -(4+1)x+4 = 0[/tex]

     [tex]x^{2} -4x-x +4 = 0[/tex]

[tex]x(x-4)-1(x-4) = 0[/tex]

       [tex](x-4)(x-1)= 0[/tex]

so, x = 4 and 1

Now,

Substitute x = 4 in (1) we get,

[tex]y = -4-4 = -8[/tex]

And putting x = 1 in (1) we get,

[tex]y = -4-1 = -5[/tex]

Hence, the solution of the given system of equation is (4,-8) and (1,-5)

Thus, Option A is the correct answer.

ACCESS MORE